2020
DOI: 10.1111/cts.12931
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Pharmacogenetic Testing Among Children’s Hospitals

Abstract: Although pharmacogenetic testing is becoming increasingly common across medical subspecialties, a broad range of utilization and implementation exists across pediatric centers. Large pediatric institutions that routinely use pharmacogenetics in their patient care have published their practices and experiences; however, minimal data exist regarding the full spectrum of pharmacogenetic implementation among children's hospitals. The primary objective of this nationwide survey was to characterize the availability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Although pediatric PGx needs extensive studies with most drugs, PGx screening may help pediatricians to adjust drug dose in order to reduce ADRs in children at risk [39]. Financial barriers (test reimbursement, test cost, and money) are the main obstacles perceived by pediatric institutions attempting clinical implementation [40]. Some countries have created Pharmacogenomics Networks for Drug Safety to develop personalized and genetic-based predictions of pediatric drug response and likelihood of experiencing ADRs [41].…”
Section: Age-related Adrsmentioning
confidence: 99%
“…Although pediatric PGx needs extensive studies with most drugs, PGx screening may help pediatricians to adjust drug dose in order to reduce ADRs in children at risk [39]. Financial barriers (test reimbursement, test cost, and money) are the main obstacles perceived by pediatric institutions attempting clinical implementation [40]. Some countries have created Pharmacogenomics Networks for Drug Safety to develop personalized and genetic-based predictions of pediatric drug response and likelihood of experiencing ADRs [41].…”
Section: Age-related Adrsmentioning
confidence: 99%
“…A recent survey of clinicians also indicated that 85% of respondents were concerned about the lack of clear guidance for clinical application [54]. This trend is troubling considering that many clinicians who use this type of test to guide clinical decision-making may not have an extensive pharmacogenetic knowledge to be sufficiently proficient in interpreting the test reports, among other perceived barriers [20,49,55]. Considering these factors, a multidisciplinary approach should be considered when interpreting pharmacogenetic test results.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2D6 genotyping can be used to ensure safe prescription of codeine for children 9 . Pharmacogenomic studies have continued to discover gene‐drug associations that are applicable to children, and more of this pharmacogenomic information continues to be used to improve pediatric pharmacotherapy 10–12 …”
Section: Pharmacogenomics In the Pediatric Clinic: Discovery And Implementation Of Dose Individualizationmentioning
confidence: 99%